PERANCANGAN APLIKASI ANDROID PENILAIAN KINERJA DAN SIKAP SPIRITUAL KARYAWAN (STUDI KASUS TOKO RETAIL IDOLMART) - Isa Faqihuddin Hanif (Prosiding Seminar Nasional Teknoka, 2019)
Mobile-based technology in the company's current activities, is something that needs to be applied in order to obtain efficiency in terms of time, without having to reduce the important components of the function of a company's activities itself. One division that needs attention in technology development is the personnel division because in managing the performance and attitudes of employees on a large scale and fluctuating nature, it requires an integrated system based on mobile that is user-friendly and able to efficiently use the appraisal tool for all employees and directors who previously used web-based system. The personnel division of Idolmart is currently running a program with a focus on employee performance appraisal, the system currently running is still desktop-based which will be developed into an Android-based mobile application. The purpose of making this application is to find empirical evidence of a positive influence on the efficiency of employee assessment programs for the Idolmart personnel division through the android application. This type of research uses qualitative research that emphasizes how the personnel section of Idolmart uses a self-development program through an android application to produce an assessment of the daily personality of its employees. The results of this study are, the output in the form of periodic table reports from all input menus can be accessed directly by employees through the android application via the view menu. The android application can be used by every Idolmart employee in accordance with the development of the upcoming Android operating system.